2015
DOI: 10.1080/00221309.2015.1009822
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effects of Facial Expression on Spatial Interference Between Gaze Direction and Gaze Location

Abstract: Gaze direction is an important social cue that interacts with facial expression. Cañadas and Lupiáñez (2012) reported a reverse-congruency effect such that identification of gaze direction was faster when a face was presented to the left but with the eyes directed to the right, or vice versa. In two experiments, this effect is replicated and then extended to explore the relationship between this effect and facial expression. Results show that the reverse-congruency effect is replicable with speeded gaze-direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 12 publications
8
35
6
Order By: Relevance
“…As in Experiment 1, participants were faster to discriminate leftward and rightward gaze presented in the periphery when that gaze was directed inward towards the central fixation object, over multiple visual eccentricities, thereby also replicating and extending prior investigations (Cañadas & Lupiáñez, 2012;Jones, 2015;Marotta et al, 2018). However, this pattern of response was reversed when participants fixated a more peripheral object, with outward rather than inward gaze being discriminated more rapidly.…”
Section: Discussionsupporting
confidence: 82%
“…As in Experiment 1, participants were faster to discriminate leftward and rightward gaze presented in the periphery when that gaze was directed inward towards the central fixation object, over multiple visual eccentricities, thereby also replicating and extending prior investigations (Cañadas & Lupiáñez, 2012;Jones, 2015;Marotta et al, 2018). However, this pattern of response was reversed when participants fixated a more peripheral object, with outward rather than inward gaze being discriminated more rapidly.…”
Section: Discussionsupporting
confidence: 82%
“…This dissociation is difficult to reconcile with the domain-general view of attentional processes. The opposite congruency effects for gaze and arrows have been replicated in subsequent experiments in our laboratory (Roman-Caballero, Marotta, Martin-Arevalo, & Lupiañez, 2017), and other studies have found that the reversed congruency effect is modulated by the emotional expression of a face when the whole face instead of just the eyes is used as the target (Jones, 2015;Torres-Marín, Carretero-Dios, Acosta, & Lupiáñez, 2017), thus supporting the social nature of the effect.…”
Section: Discussionsupporting
confidence: 70%
“…It may be possible for gelotophobes to respond to happy faces in the same way they would respond to fear faces, that is, as an avoidance-oriented emotion. Additionally, to corroborate the adequacy of the “approach or avoidance oriented emotions” interpretation for the reverse congruency (i.e., eye contact) effect that Jones (2015) proposed, and to extend our understanding of the role of emotional expression in the modulation of gaze discrimination, we decided to incorporate faces portraying sadness into our experiment. In accordance with Jones (2015) , we expected to replicate the previous results in happiness, anger, neutral, and fear stimuli; regarding sadness, we expected to find a pattern similar to fearful faces and different from angry or happy faces.…”
Section: Methodsmentioning
confidence: 96%
“…This reverse congruency effect—classical results with non-social stimuli, such as arrows, show faster responses for congruency trials—was interpreted in terms of eye contact (e.g., responses are faster when a face located to the left looks to the right, i.e., at us). Moreover, further investigation revealed that the emotional charge of the facial expression modulated this eye contact effect ( Jones, 2015 ). More specifically, Jones’s results indicated that the effect was stronger for happy and angry faces (approach-oriented emotions) than for neutral faces, and it was non-existent for fearful faces (avoidance-oriented emotions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation